2016
DOI: 10.1016/j.joa.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of atorvastatin in prevention of atrial fibrillation after heart valve surgery in the PROFACE trial (PROphylaxis of postoperative atrial Fibrillation After Cardiac surgEry)

Abstract: BackgroundTo evaluate the efficacy of perioperative atorvastatin administration for prophylaxis of postoperative atrial fibrillation (POAF) after heart valve surgery.MethodsOur study included 90 patients with heart valve disease who were scheduled to undergo elective cardiac surgery. Cases with previous AF or preoperative beta-blocker therapy were excluded. Patients were randomized into the atorvastatin group, which included 47 patients who received 40 mg/day of atorvastatin 7 days before and after the surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
6
0
4
Order By: Relevance
“…Among all 22 studies, 18 trials with 3995 participants reported the outcome of POAF, and nine with 3214 patients reported AKI. 14 RCTs enrolled patients undergoing CABG, three RCTs undergoing valve surgery 13 , 23 , 26 . For studies only involving patients with CABG, five of them were with CPB 17 , 21 , 24 , 25 , 32 , three with off-pump 8 , 17 , 30 , and six with CPB or off-pump 19 , 20 , 22 , 28 , 29 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Among all 22 studies, 18 trials with 3995 participants reported the outcome of POAF, and nine with 3214 patients reported AKI. 14 RCTs enrolled patients undergoing CABG, three RCTs undergoing valve surgery 13 , 23 , 26 . For studies only involving patients with CABG, five of them were with CPB 17 , 21 , 24 , 25 , 32 , three with off-pump 8 , 17 , 30 , and six with CPB or off-pump 19 , 20 , 22 , 28 , 29 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Rizikové faktory POAF, ktoré nachádzame v literatúre, zahŕňajú elektrické, metabolické, neurohumorálne a zápalové zmeny, ktoré narúšajú geometriu a elektrofyziológiu srdca. 9 Tieto faktory môžeme rozdeliť na faktory spojené s pacientom a faktory spojené s chirurgickou intervenciou (tabuľka 1). 6 Veľa štúdií sa zameriava na vznik POAF po bypassovej operácii srdca, alebo operáciách mitrálnej chlopne.…”
Section: úVodunclassified
“…Tento výsledok koreluje s prácou autorov Carrascal a spol., ktorí taktiež nepotvrdili vplyv statínov na zníženie incidencie POAF pri izolovanej operácii chlopní. 9 Zväčšenie LA je dôsledok chronického zvýšenia plniacich tlakov v ľavých oddieloch srdca a komorovej diastolickej dysfunkcie. Mosquera a spol.…”
Section: Diskusiaunclassified
“…V literatúre je uvádzaných viacero liekov ako možná prevencia vzniku pooperačnej AF. Najčastejšie sa uvádzajú -blokátory, Ca-blokátory, vitamín C, sotalol, atorvastatín a amiodaron [3,14,22,23]. Zápalová teória vzniku pooperačnej AF vysvetľuje predoperačné podávanie prednizonu, ako prevenciu AF [14].…”
Section: Mvrtvrtransseptunclassified
“…Na druhej strane niektorí autori prezentujú protektívny účinok atorvastatinu len pri bypasovej operácii nie pri operačnom výkone na mitrálnej chlopni. [22,25]. Pozitívny účinok aplikovania vitamínu C na redukciu pooperačnej AF sa však podľa literatúry už pozitívne neprenáša na skrátenie hospitalizácie, alebo celkovo nižšej morbidite [23].…”
Section: Mvrtvrtransseptunclassified